Unilateral biportal endoscopic lumbar interbody fusion enhanced the recovery of patients with the lumbar degenerative disease compared with the conventional posterior procedures: A systematic review and meta-analysis - Yang, Honghao; Cheng, Fengqi; Hai, Yong; Liu, Yuzeng; Pan, Aixing (Frontiers in Neurology, 2023)
Background: Minimally invasive endoscopic technique is an important component of ERAS protocol for neurosurgery. The unilateral biportal endoscopic lumbar interbody fusion (ULIF) has been used in the treatment of lumbar degenerative diseases (LDD). This study aims to investigate whether ULIF could enhance the recovery of patients with LDD compared with the conventional minimally-invasive transforaminal lumbar interbody fusion (MI-TLIF) or posterior lumbar interbody fusion (PLIF). Methods: A comprehensive literature search was performed for relevant studies in PubMed, EMBASE, Web of Science, Cochrane Library database, China National Knowledge Internet, and Wanfang database. Surgical data, clinical outcomes, radiographic outcomes, and surgical complications were compared between patients with LDD who underwent ULIF and those who underwent conventional MI-TLIF or PLIF. Results: Twelve studies, comprising 981 patients with LDD, were included. Compared with MI-TLIF, ULIF group presented a significantly reduced EBL (WMD, -106.00; 95% CI -140.99 to -71.10, P < 0.001) and shorter LOS (WMD, -1.27; 95% CI -1.88 to -0.66, P < 0.001); better short-term improvement in ODI (WMD, -2.12; 95% CI -3.53 to -0.72, P = 0.003) and VAS-BP (WMD, -0.86; 95% CI -1.15 to -0.58, P < 0.001). Compared with PLIF, ULIF group presented a significantly reduced EBL (WMD, -149.22; 95% CI -284.98 to -13.47, P = 0.031) and shorter LOS (WMD, -4.40; 95% CI -8.04 to -0.75, P = 0.018); better short-term improvement in VAS-BP (WMD, -1.07; 95% CI -1.77 to -0.38, P = 0.002) and VAS-LP (WMD, -0.40; 95% CI -0.72 to -0.08, P = 0.014); enhanced short- and long-term improvement in ODI at one month postoperatively (WMD, -3.12; 95% CI -5.72 to -0.53, P = 0.018) and the final follow-up (WMD, -1.97; 95% CI -3.32 to -0.62, P = 0.004). Conclusion: ULIF was associated with reduced EBL, shorter LOS, and comparable fusion rate as well as complication management. Compared with MI-TLIF, a better short-term improvement in VAS-BP and ODI was achieved by ULIF; compared with open PLIF, additional enhanced short-term improvement in VAS-LP and long-term improvement in ODI was observed in ULIF. ULIF could enhance the recovery of patients with LDD compared with the conventional posterior procedures.